New triterpene isovanniloyl and antibacterial activity of constituents from the roots of Paullinia pinnata Linn (Sapindaceae) - A.A. Lasisi; B.W. Ayinde; A.O. Adeleye; P.A. Onocha; I.A. Oladosu; P.A. Idowu (Journal of Saudi Chemical Society)
In addition to lupeyl steryl ether (1) and 3-oxo-11α-hydroxyl-20 (29) lupen (2), a new lupeol-3-isovanniloyl ester (3) was isolated from Paullinia pinnata. Using detailed 1D and 2D NMR spectra and comparison with the published data, the new compound was characterised as 3-O-isovanilloyl-3R,5R,8R,9R,10R,13R,14S,17S,18R,19R-lup-20(29)-en, for which the trivial name Paullinoyl was proposed. Compound 3 demonstrated significant antibacterial activity on the tested strains (MIC 15.2–30.20 μg/ml). The antibacterial activities obtained in this study confirmed the use of P. pinnata in traditional medicine for treating bacterial infections.